Ideological Manifestations in Tennessee Williams’ Selected Plays - Ghanbari , Pegah; Hanif, Mohsen (Jordan Journal of Modern Languages & Literatures, 2025)
Tennessee Williams (1911-1983), the spokesman of the marginalized, devoted part of his oeuvre to unearthing and eradicating social injustice. Taking advantage of Critical Discourse Analysis (CDA), this study draws on textual and contextual clues to address the playwright’s critique of unequal social orders. CDA exposes the intricate operations of power and ideology in maintaining hierarchically gendered social orders and institutionalized power asymmetries. The goal of CDA is to lay bare the subtle ways in which gendered assumptions and hegemonic power relations are discursively produced, maintained or negotiated. By deploying Fairclough’s three-dimensional model which explores the interconnection between social practices, discursive practices and its textual manifestation, the present paper aims to delve into implicit ideological effects of language and influence of power relations embedded in the discourse of Williams’ selected plays, including A Streetcar Named Desire (1947), Cat on a Hot Tin Roof (1955) and The Night of Iguana (1961), to expose the role of discourse in the maintenance of power. Keywords: Critical Discourse Analysis; Ideology; Discourse; Fairclough; Patriarchy.